Improving the laboratory diagnosis of TB in Ghana: The impact of a quality assurance system - Addo, K.K.; Dan-Dzide, M.; Yeboah-Manu, D.; Owusu-Darko, K.; Caulley, P.; Minamikawa, M.; Ofori-Adjei, D. (International Journal of Tuberculosis and Lung Disease, 2006)
SETTING: Greater Accra region, Ghana. OBJECTIVE: To establish a pilot quality assurance (QA) system in sputum smear microscopy and to evaluate its impact. DESIGN: Quarterly supporting visits were paid to participating laboratories between 2000 and 2002. Fifteen examined slides were selected randomly from each laboratory during the visits and blindly re-assessed. Feedback was given promptly to the various laboratories. Training and stakeholder workshops were organised whenever necessary. RESULTS: General improvements in smear preparation and staining as well as the reading ability of the laboratory personnel included in the study were observed. The average marks for specimen quality, staining ability, smear cleanness, thickness, size and evenness increased from 64%, 79%, 69%, 46%, 67% and 60% in the last quarter of 2000 to 81%, 90%, 86%, 79%, 80% and 74%, respectively, 24 months after the establishment of the QA system. Within the same period, the rate of false-positives and -negatives decreased from respectively 14.8% and 20.5% to 0%, and agreements in positivity grade increased from 74% to 95%. The performance of the participating laboratories in keeping the laboratory registers up to date also improved. CONCLUSION: The QA system needs to be extended to the rest of the country.